Two-dimensional ultrathin surfactant-encapsulating polyoxometalate assemblies as carriers for monodispersing noble-metal nanoparticles with high catalytic activity and stability. Issue 5 (19th January 2021) - Ji, Xing-Yu; Yu, Fei-Yang; Li, Ying-Qi; Zhu, Hao-Tian; Zhao, Hui-Ying; Shi, Yue; Wang, Yong-Hui; Tan, Hua-Qiao; Li, Yang-Guang
Abstract : The Ag/DODA-PMo12 composite demonstrates a high catalytic efficiency in the catalytic reduction of 4-nitrobenzene. Abstract : Noble metal nanoparticles (NMNPs) with excellent catalytic activity and stability play an important role in the field of environmental governance. A uniform distribution and a strong binding force with the carriers of the noble metal nanoparticles are important, but avoidance of the use of additional reducing agents is a promising direction of research. Herein, 2D ultrathin surfactant-encapsulating polyoxometalate (SEP) nanosheets constructed by the self-assembly of dodecyldimethylammonium bromide (DODA) and molybdophosphate (H3 PMo12 O40, PMo12 ) are designed to be versatile carriers for Ag nanoparticles. Under the synergistic effect of the well-arranged PMo12 units, encapsulating hydrophobic oleic acid (OA) and reductive molybdophosphate under Xe lamp irradiation, the silver oleate (AgOA)-derived Ag nanoparticles (5 ± 2 nm) are monodispersed on the DODA-PMo12 assemblies and form the Ag x /DODA-PMo12 composite. The optimized Ag4.89 /DODA-PMo12 composite exhibits high catalytic activity and stability in the degradation of 4-nitrophenol (4-NP), which reaches a superior rate constant of 6.49 × 10 –3 s −1 and without significant deterioration after three recycles. This technique can be facilely promoted to other noble metal nanoparticles with excellent catalytic activity and stability.